Information Management Skills Required by the Minority Libraries in Kolkata and Hooghly Districts, West Bengal - Kayal, Soumen; Bandopadhyay, Somnath; Banerjee, Swapna (DESIDOC Journal of Library & Information Technology, 2015)
Information is an essential ingredient in our life. Serving the right information to the right users at the right time is the goal of every library and information centre. It has become necessary to manage this information in a systematic way to achieve the goal. The process of management of a library requires skills at various levels. These skills, though relatively independent of one another, blend together to bring about organisational productivity, efficiency, and harmony. There are a number of libraries governed by minority communities in West Bengal. These libraries are playing remarkable role in the dissemination of information. This article highlights and discusses the skills of information/management and its dissemination in the various minority-governed libraries, and also explores the collection, arrangement, and management of these libraries.